Use of External Tissue Expanders to Assist in Reverse Sural Flap Donor Site Closure. Issue 6 (June 2021) - Cox, Cameron; Gaschen, Paul D.; Foley, David; MacKay, Brendan
Abstract : Background: Complex lower extremity injuries can cause large soft tissue defects that require reconstruction. In the distal third of the lower leg, the reverse sural artery fasciocutaneous flap is a viable coverage option due to its versatility, vascular supply, and ability to cover larger defects than other local pedicled flaps. Although advances in techniques have improved reliability of reverse sural flaps, complications such as donor site morbidity remain a challenge for surgeons. Donor wounds may be difficult to close, and delayed closure can increase the risk for infection and other postoperative complications. In these cases, donor site skin grafting can cause additional morbidity and/or mobility restrictions. Methods: In this case series, 16 patients underwent reconstruction with large reverse sural artery fasciocutaneous flaps and a continuous external tissue expander to assist in donor site closure. Results: One patient was lost to follow-up. All donor sites healed without complication with an average time to healing of 9.2 weeks (n = 15, range: 3–18). At the most recent follow-up, all flaps survived without complication. Conclusions: Given our success in 100% of patients, we purport that this system of enhanced closure may be a valuable adjunctive therapy in closing reverse sural artery fasciocutaneous flaps. We believe that this method may be useful in closing other difficult donor wounds.